Cytotoxicity Test of Bandotan Herbal Ethanol Extract (Ageratum conyzoides L.) Using the Brine Shrimp Lethality Test (BSLT) Method - Sari, Farida; Ridwanto, Ridwanto; Daulay, Anny S.; Rani, Zulmai (Universitas Tadulako, 2024)
Cytotoxic activity is a process that can induce cell death. One of the plants that has cytotoxic properties is bandotan (Ageratum conyzoides L.). The purpose of this study was to identify the class of secondary metabolites present in the ethanol extract of Bandotan herb and to evaluate its cytotoxicity by determining the LC50 value using the Brine Shrimp Lethality Test (BSLT) method. This research includes phytochemical screening and cytotoxicity testing of an ethanol extract of Herba bandotan using the BSLT method. BSLT is the first method for cytotoxicity testing using Artemia salina Leach larvae at the nauplii stage. Used in the BSLT method because it has similar responses with mammals, namely DNA-dependent RNA polymerase in Artemia salina Leach, similar to DNA-dependent RNA polymerase in mammals. By phytochemical screening, the secondary metabolites in Herba Bandotan (Ageratum conyzoides L.) are alkaloids, flavonoids, saponins, steroids, and tannins. Based on the results of the cytotoxicity test using the BSLT method, it shows that the ethanol extract of Herba bandotan (Ageratum conyzoides L.) has the potential to be anti-cancer because it has an LC50 value of 255.1915 g / mL, which is included in the toxic category and has the potential to be anti-cancer. Potential as an anticancer agent in the BSLT test if it has an LC50 value < 1000 µg / mL.